The High-Effective Catalytic Degradation of Benzo[a]pyrene by Mn-Corrolazine Regulated by Oriented External Electric Field: Insight From DFT Study - Long, Tairen; Wan, Haiyan; Zhang, Jianqiang; Wu, Jie; Liang, Jin-Xia; Zhu, Chun (Frontiers in Chemistry, 2022)
The degradation of BaP to hydroxybenzo[a]pyrene by Mn-corrolazine and its regulation by oriented external electronic field (OEEF) are systematically studied using the first-principle calculations. Extensive density function calculations show the degradation of BaP to hydroxybenzo[a]pyrene by Mn-corrolazine goes through three-step process in the absence of OEEF, in which more toxic and stable epoxide intermediates is generated. However, with the application of the OEEF along the intrinsic Mn-O reaction axis, the degradation process of BaP to hydroxybenzo[a]pyrene is greatly simplified. When the OEEF is applied, the negative charge of the terminal O atom of Mn-OO corrolazine increase with the increase of the OEEF intensity. As the intensity of the OEEF increases to more than 0.004 a.u., the negatively charged terminal O has ability to directly abstract the positively charged H atom of BaP, so the degradation of BaP to hydroxybenzo[a]pyrene can be completed through one-step process, thus avoiding the production of more toxic epoxide intermediates.